Developing the reading habits of secondary school students in Nigeria: the way forward (2018)
In recent times, lack of cultivating the habit of reading has been the concern of all stakeholders. The lack of enthusiasm of secondary school students for reading has contributed to many failures such as poor writing and limited understanding about what they are taught in class. This growing concern provides motivation for this study. Thus, this study seeks to discover and elucidate the various ways whereby secondary school students in Nigeria could develop the habits of reading amidst divergent distractions around them especially in the 21st Century society as well as the roles of stakeholders towards enhancing the reading habits of students at the secondary school. The study concluded that the reading habits of secondary school students should be given rapt attention because of the imminent danger of losing reading habits in the era of Information and communication technologies, where the use of social media sites is the Order of the day. The study recommends that there must be a fixed time for reading a variety of reading materials that will appeal to students and that adopting different methods to arouse the interest of students could enhance their reading habits.